ChemInform Abstract: Catalytic Cross Deoxygenative and Dehydrogenative Coupling of Aldehydes and Alkenes: A Redox‐Neutral Process to Produce Skipped Dienes. Issue 8 (25th February 2014) - Qian, Bo; Zhang, Guoying; Ding, Yongzheng; Huang, Hanmin
Abstract 24 examples